Evil: a critical primer - MacKendrick, Kenneth G. (Concepts in the study of religion, 2023)
"Evil: A Critical Primer argues that our colloquial conception of evil, as related exclusively to the moral domain, is usefully illuminated by attending to historical and cultural context and cross-cultural comparison"--